2004
DOI: 10.1002/mds.20113
|View full text |Cite
|
Sign up to set email alerts
|

Does parkin play a role in the peripheral nervous system? A family report

Abstract: Two genes were identified for autosomal recessive forms of early onset Parkinson's disease: parkin and DJ-1. We describe 2 siblings with EOPD due to parkin mutations and peripheral neuropathy, which presented as neuropathy with liability to pressure palsies (HNPP) in the index case. RT-PCR experiments revealed that the parkin gene is expressed in sural nerves from both controls and patient with parkin-related disease. Our findings support the view that parkin may play a role in the peripheral nervous system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 19 publications
1
35
0
Order By: Relevance
“…First, our study points that autonomic small myelinated and unmyelinated fibers are relatively well preserved in PARK2 mutation carriers compared to iPD and E46K mutation patients. Second, previous clinical studies in PARK2 carriers have reported a specific damage of large diameter nerve fibers, including peripheral neuropathy in two siblings with PARK2 mutation [15] and a diminished amplitude of sural sensory nerve action potential in nine PARK2 carriers [26]. Moreover, a study by Hase et al in bovine peripheral nerves demonstrated the presence of parkin protein in the axoplasm and in Schwann cells of large diameter myelinated nerve fibers [14], supporting that parkin plays different roles in the normal physiology of the nervous system, not only in CNS but also in peripheral nervous system.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…First, our study points that autonomic small myelinated and unmyelinated fibers are relatively well preserved in PARK2 mutation carriers compared to iPD and E46K mutation patients. Second, previous clinical studies in PARK2 carriers have reported a specific damage of large diameter nerve fibers, including peripheral neuropathy in two siblings with PARK2 mutation [15] and a diminished amplitude of sural sensory nerve action potential in nine PARK2 carriers [26]. Moreover, a study by Hase et al in bovine peripheral nerves demonstrated the presence of parkin protein in the axoplasm and in Schwann cells of large diameter myelinated nerve fibers [14], supporting that parkin plays different roles in the normal physiology of the nervous system, not only in CNS but also in peripheral nervous system.…”
Section: Discussionmentioning
confidence: 98%
“…In addition, a number of case reports in PARK2-positive PD patients have noted normal 123I-MIBG scans [12,13,8] and preserved TH-immunoreactive fibers in the epicardium [12]. While these findings support the view that small myelinated and unmyelinated autonomic nerve fibers are preserved in PARK2 mutation carriers, this hypothesis contrasts with the presence of parkin protein in the axoplasm of bovine myelinated nerve fibers and Schwann cells [14] and with the presence of peripheral neuropathy in PARK2 mutation carriers [15].…”
Section: Introductionmentioning
confidence: 90%
“…Another presented 30 years after disease onset with neuropathy with liability to pressure palsies. NCS and sural nerve biopsy showed a motor and sensory neuropathy [2]. Another, 24 years after disease onset, had a sensory axonal neuropathy on NCS [3].…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…[7][8][9][10] In our series of PARK2, only two patients showed subjective sensory symptoms. However, eight of nine patients exhibited marked reductions in the sural SNAP amplitude, even in the absence of sensory symptoms.…”
mentioning
confidence: 60%